Distinguishing the Need to Belong and Sense of Belongingness: The Relation between Need to Belong and Personal Appraisals under Two Different Belongingness-Conditions - Saga Pardede; Velibor Bobo Kovač (MDPI AG, 2023)
People are frequently caught in the hold between the need to belong and the fear of exclusion. However, these needs might be expressed differently under different belongingness conditions, where other powerful social processes are accentuated. Thus, the need to belong and social exclusion are concepts that are subjectively appraised based on one's social relations. The present study aims to examine the relationship between the need to belong and five personal appraisals under two different belongingness conditions: (1) social-emotion support and (2) social-value representation. A total of 201 participants from two different groups were presented with 69 different items measuring five personal appraisals (exclusion, shame, social-worthiness, emotional self-expression, and prosocial-relating behaviour). Condition 2, social-value representation with social worthiness being appraised, offered the strongest connection as a significant predictor amongst all appraisals in both conditions, despite both exclusion and shame being indicated as significant predictors, to begin with. Thus, highlighting the appraisal of social worthiness in support of one's need to socially represent oneself by not being compared to others while being valued as an alternative motive for realising a sense of belongingness. The empirical and theoretical limitations and implications are also discussed.